The influence of surface parameters of coatings deposited by various vacuum-plasma methods on the cell/material interaction in vitro tests - Zykova, A.; Safonov, V.; Luk’yanchenko, V.; Walkowicz, J.; Rogowska, R. (Вопросы атомной науки и техники, 2007)
The surface of an implant plays a basic role in determining biocompatibility and integration due to its direct contact with the adjacent tissues. There is now the good understanding that life time of orthopedic implants and the design of the novel tissue-engineering medical products may be associated with local and remote biological tissue response and cell-material interaction. Material properties such as implant surface composition, roughness, topography can influence events at bone –implant interfaces and cell response to implant material. Поверхневі властивості функціональних покриттів, що широко застосовані у сучасній медицині, мають визначне значення при оцінці їх біосумісності. Термін використання існуючих ендопротезів та дизайн нових біоінженерних розробок безпосередньо зв’язані з локальним та віддаленим впливом взаємодії біоматеріалів та біологічних тканин. Поверхневі характеристики, такі як склад, шорсткість, поверхнева енергія мають прямий вплив на процеси взаємодії з тканинами організму на клітинному рівні. Поверхностные свойства функциональных покрытий, широко применяемых в современной медицине, играют определяющую роль при оценке их биосовместимости. Срок службы существующих эндопротезов и дизайн новых биоинженерных разработок непосредственно связаны с локальными и отдаленными последствиями взаимодействия биоматериалов и биологических тканей. Поверхностные характеристики, такие как состав, шероховатость, поверхностная энергия оказывают прямое воздействие на процесс взаимодействия с тканями организма на клеточном уровне.